Convergence Dynamics in Polish Voivodships (Research Bulletins of the Faculty of Economic Sciences, 2018)
The main aim of this article is to analyze cohesion policy and its impact on available social, economic and spatial resources that counteract excessive regional differentiation of Polish voivodships. When assessing the research problem, it is necessary to focus attention on the general policy of regional development and its impact on the convergence process (reducing disparities). For research purposes, an internet interview was conducted, and the data collected by the Główny Urząd Statystyczny (GUS) were used - to indicate where the problem is in the field of effective implementation of cohesion policy. Within two weeks, 49 people who live in the Małopolskie Voivodeship, in the age range 18 to 55, answered questions related to the policy of cohesion policy, regional policy and local government units. In combination with GUS information, research results indicate that the problem is in territorial units located within the province. The survey also reveals that the biggest setback in the effective implementation of the cohesive politics is the way local territorial autonomies function. In Poland, however, local governments have not yet established the two-fold purpose. This means the process of convergence cannot be seen as success, and very often it actually brings quite opposite effects. Although total convergence of voivodship is impossible due to the territorial differences, some positive influence of the convergence can be seen in other areas of social life, e.g.: social, transport or environmental infrastructure or employment. In order to maintain the constant growth and development of all voivodships in Poland, both local and regional governments need to focus on the implementation of ‘growing together’ through internal and external development.
Keywords: convergence, regional politics, voivodship, local territorial autonomies, cohesive politics